SHV-13, a Novel Extended-Spectrum β-Lactamase, in Klebsiella pneumoniae Isolates from Patients in an Intensive Care Unit in Amsterdam - Yuan, Meifang (American Society for Microbiology, 2000)
Eleven clonally related Klebsiella pneumoniae isolates were examined. These had been isolated at an intensive care unit in Amsterdam in 1994. Their resistance was associated with a conjugative 170-kb plasmid which encoded a novel SHV β-lactamase designated SHV-13. The SHV-13 enzyme had two substitutions compared with SHV-1: Leu35Gln and Gly238Ala. It hydrolyzed cefotaxime much more rapidly than ceftazidime or aztreonam.